2019
DOI: 10.1037/ser0000315
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-informed care in a patient-centered medical home for adolescent mothers and their children.

Abstract: Adolescent mothers experience higher rates of trauma and abuse, as well as increased risks for mental health disorders, compared to adolescent girls who are not mothers, making them a particularly vulnerable population and contributing to them feeling less supported by or allied with their medical provider. Women with a history of childhood abuse face increased rates of obstetric complications; their infants are at increased risk for low birthweight, developmental and intellectual delays, and behavioral proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…Once trust has been established, the open and genuine connection between the service user and the service provider allows the opportunity for the service user to share their experiences in a safe and nonjudgmental space (Kirst et al, 2017;Reeves, 2015). This finding has been validated in studies such as an evaluation of a Colorado maternity program conducted by Ashby et al (2019), which found that a safe and trustworthy clinic environment led to an increased number of visits by service users.…”
Section: Trustmentioning
confidence: 88%
“…Once trust has been established, the open and genuine connection between the service user and the service provider allows the opportunity for the service user to share their experiences in a safe and nonjudgmental space (Kirst et al, 2017;Reeves, 2015). This finding has been validated in studies such as an evaluation of a Colorado maternity program conducted by Ashby et al (2019), which found that a safe and trustworthy clinic environment led to an increased number of visits by service users.…”
Section: Trustmentioning
confidence: 88%
“…Hispanic adolescents are three times more likely to experience PPD compared with adult counterparts and are more likely to drink alcohol (Nunes & Phipps, 2013). Adolescent mothers have also been shown to experience higher rates of trauma and abuse (Ashby, Ehmer, & Scott, 2019). The Colorado Adolescent Maternity Program is one model that serves this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…The Colorado Adolescent Maternity Program is one model that serves this vulnerable population. It provides trauma-informed care, mental health, and parenting assistance girls through the age of 22 years (Ashby et al, 2019). More models that address this vulnerable population are desperately needed.…”
Section: Discussionmentioning
confidence: 99%
“…Two major differences between the results of the two searches are evident. In contrast to the primary search, most of the 10 studies identified in the secondary search were conducted in high-income countries, including five in the United States [70][71][72][73][74]. In addition, cluster-randomized controlled trials were the most common study design identified in the primary search, but only three of the 10 studies identified in the secondary search randomized participants [72,75,76].…”
Section: Secondary Search: Strategies To Improve Retention Among Adolescents Regardless Of Hiv Statusmentioning
confidence: 99%